2004
DOI: 10.1095/biolreprod.104.029652
|View full text |Cite
|
Sign up to set email alerts
|

Theca Interna: The Other Side of Bovine Follicular Atresia1

Abstract: Currently, histological classifications of ovarian follicular atresia are almost exclusively based on the morphology of the membrana granulosa without reference to the theca interna. Atresia in the bovine small antral ovarian follicle has been redefined into antral or basal atresia where cell death commences initially within antral or basal regions of the membrana granulosa, respectively. To examine cell death in the theca interna in the two types of atretic follicles, bovine ovaries were collected and process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
1
24
0
4
Order By: Relevance
“…We observed that periantral cells die by pycnosis or apoptosis and are phagocytosed and removed by neighbouring granulosa cells, as demonstrated previously (Byskov 1979, Van Wezel et al 1999. Peribasal cells, on the other hand, did not become apoptotic, but rather differentiated morphologically and functionally into Gene expression in the theca of bovine follicles 459 luteal-like cells, which lost the ability to express follistatin, but instead expressed StAR (present study) and P450 sidechain cleavage (Clark et al 2004). It has been hypothesized that there are two types of atresia in small bovine follicles: basal and antral , Clark et al 2004.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We observed that periantral cells die by pycnosis or apoptosis and are phagocytosed and removed by neighbouring granulosa cells, as demonstrated previously (Byskov 1979, Van Wezel et al 1999. Peribasal cells, on the other hand, did not become apoptotic, but rather differentiated morphologically and functionally into Gene expression in the theca of bovine follicles 459 luteal-like cells, which lost the ability to express follistatin, but instead expressed StAR (present study) and P450 sidechain cleavage (Clark et al 2004). It has been hypothesized that there are two types of atresia in small bovine follicles: basal and antral , Clark et al 2004.…”
Section: Discussionmentioning
confidence: 49%
“…Peribasal cells, on the other hand, did not become apoptotic, but rather differentiated morphologically and functionally into Gene expression in the theca of bovine follicles 459 luteal-like cells, which lost the ability to express follistatin, but instead expressed StAR (present study) and P450 sidechain cleavage (Clark et al 2004). It has been hypothesized that there are two types of atresia in small bovine follicles: basal and antral , Clark et al 2004. Alternatively, we suggest that these are consecutive stages of the atretic process: in the early stage of atresia, periantral granulosa cells die by apoptosis or pyknosis and are removed from the follicle.…”
Section: Discussionmentioning
confidence: 49%
“…This may be because the granulosa cells that do not receive direct oxygenation are more sensitive to anoxia than theca cell layer (Rodgers and Irving-Rodgers, 2010) and, therefore, the granulosa cells undergo apoptosis earlier (Rosales-Torres and Guzman, 2008). Several authors have shown that during atresia of bovine follicle, apoptosis occurs earlier in the granulosa cells then in the theca cell layer (Clark et al, 2004). These studies could explain why differences in CER concentrations between healthy and atretic follicles were found in the granulosa cells, but not in the theca cell layer.…”
Section: Discussionmentioning
confidence: 92%
“…During follicle growth, different cell(s) may vary in their susceptibility to death and if these cells are irreplaceable then this would result in follicular atresia. At the bovine preantral stage, oocytes are reported to be the first to die (Rajakoski 1960), in contrast to the antral stage where granulosa cells die first, and in one form of atresia (discussed below) thecal cells, including steroidogenic and endothelial cells (Clark et al 2004), also die very early in atresia. When atresia is initiated by a large amount of cell death, this could be due to loss of growth factor support such as TGFa (Wang et al 2002), or that expression of Fas or Fas ligand (Porter et al 2000, Quirk et al 2004) could be involved in initiating the process.…”
Section: Which Cell(s) Die First Andmentioning
confidence: 99%